Dual tumour–myeloid targeting of glioblastoma with GPNMB CAR-T cells - Neil Savage; Shan Grewal; Muhammad Vaseem Shaikh; Franz J. Zemp; Dillon Mckenna; Nicholas Mikolajewicz; Hinda Najem; Joanna Pyczek; Jiuran Wei; Mohamed A. B. Taleb; Lucas C. Asselstine; Alisha Anand; et al. (Nature, 2026)
Abstract Glioblastoma is a lethal brain tumour for which current multimodal treatment rarely prevents recurrence 1 . Therapeutic failure is driven by extensive intratumoural cellular heterogeneity 2 with a microenvironment dominated by tumour-associated macrophages that sustain tumour growth and immunosuppression 3 . Although chimeric antigen receptor (CAR)-T cell therapies are being developed for glioblastoma, sustained response has been undermined by non-uniform antigen expression, antigen loss and microenvironmental barriers that are not directly engaged by tumour-targeting designs 4 . These limitations motivate new strategies that address the disease as a coupled tumour–immune system rather than a single malignant compartment. Here we use a multi-omic target discovery platform to identify GPNMB as a dual-compartment antigen in glioblastoma. Anti-GPNMB CAR-T cells showed potent anti-tumour activity, with long-term disease control in orthotopic patient-derived xenografts and syngeneic glioma models through concomitant depletion of GPNMB + tumour and immunosuppressive myeloid populations. By collapsing tumour control and microenvironmental reprogramming, these findings provide a new strategy for antigen selection and targeting in heterogenous, myeloid-rich solid cancers.